Efficient and pure femtosecond-pulse-length source of polarization-entangled photons - Weston, MM; Chrzanowski, HM; Wollmann, S; Boston, A; Ho, J; Shalm, LK; Verma, VB; Allman, MS; Nam, SW; Patel, RB; Slussarenko, S; Pryde, GJ (Optical Society, 2016)
We present a source of polarization entangled photon pairs based on spontaneous parametric downconversion engineered for frequency uncorrelated telecom photon generation. Our source provides photon pairs that display, simultaneously, the key properties for high-performance quantum information and fundamental quantum science tasks. Specifically, the source provides for high heralding efficiency, high quantum state purity and high entangled state fidelity at the same time. Among different tests we apply to our source we observe almost perfect non-classical interference between photons from independent sources with a visibility of (100 ± 5)%.